Evaluasi Kebijakan Perlombaan Desa Tingkat Provinsi di Provinsi Kalimantan Utara - Agus Perdiansyah; Yayan Mulyana; Agus Joko Purwanto (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This thesis examines the evaluation of the Provincial Village Competition Policy in North Kalimantan Province, focusing on its implementation and impact as per the Indonesian Ministry of Home Affairs Regulation No. 81 of 2015. It highlights the importance of rural development for enhancing the welfare of North Kalimantan's residents. While rural development aims to improve living standards and sustainably utilize natural resources, villages often face challenges like poverty and inadequate infrastructure. The Provincial Village Competitions serve as a strategy to boost rural development. This research uses a descriptive, qualitative approach employing policy evaluation theory. It involves stakeholders engaged in executing this policy, analyzing data through NVivo software. The study uncovers obstacles hindering village participation in these competitions despite North Kalimantan's potential. Factors such as individual motivation, insufficient preparation, and administrative shortcomings contribute to reduced involvement. The evaluation process comprises pre-competition, event execution, and assessment stages, determining winning villages based on specific criteria. Although regulations support these competitions, participation rates have declined, posing a significant concern. The research suggests improvements to enhance the Provincial Village Competition implementation, aiming for sustainable rural development and bettering the lives of North Kalimantan's rural communities.